The great story and the great commission : participating in the biblical drama of mission - Wright, Christopher J. H., 1947- (Acadia studies in Bible and theology, 2023)
"A highly-regarded scholar and speaker offers a succinct treatment of the Bible's grand narrative and how this influences believers' understanding of their mission in the world"--